PENGARUH DIVERSITY AND EQUAL OPPORTUNITY, GREEN STRATEGY, DAN GREEN COMMITMENT TERHADAP PENGUNGKAPAN LAPORAN KEBERLANJUTAN PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA DAN SINGAPURA - Nuraini, Yenni; Lastanti, Hexana Sri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
Sustainability report are one of the important instruments in environmental, social and government reporting in companies. Disclosure of sustainability reports can reflect how the company contributes in efforts to implement sustainable commitments and strategies. Several factors that can encourage companies to disclose sustainability reports are diversity and equal opportunity, green strategy, and green commitment. This research aims to analyze whether there is an influence of diversity and equal opportunity, green strategy, and green commitment towards disclosure of sustainability reports, based on the Global Reporting Initiative (GRI) G4. The analysis technique used in the research is a multiple linear regression method. The research design is quantitative causality supported by secondary data. The sampling technique uses a purposive sampling method which focuses on 105 obsevation data with sample of companies listed on the Indonesian Stock Exchange and Singapore Stock Exchange in the transportation and logistics sector throughout the period 2018 – 2022. The results of panel data model tests, hypothesis testing, and multiple regression analysis show that both green commitment and diversity & equal opportunity aspects have a positive effect the disclosure of sustainability reports, while green strategy has a negative effect the disclosure of sustainability reports. Therefore, it is recommended to conduct further research to find out why green strategy has a negative effect on sustainability report disclosure.